Pengembangan Media Sosial sebagai New Media Informatif sebagai Upaya Peningkatan Pengetahuan Remaja tentang HIV-AIDS - Ummu Muntamah; Fiktina Fivri Ismiryam (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2018)
This research is based on the still high incidence of HIV-AIDS in Indonesia. Until now HIV-AIDS cases have been reported by 341 of 497 districts / cities in 33 provinces. In addition, Indonesia is one of the countries in Asia with the fastest growing HIV / AIDS epidemic. Based on the results of the Review of HIV / AIDS workshop, problems were found that 1) the institution was not optimal and the coordination was weak and institutional networks that deal with HIV / AIDS prevention and control, 2) lack of access to quality services, 3) lack of strategies and methods of communication, information and the right education (IEC) about HIV / AIDS. These factors have caused lack of knowledge about HIV-AIDS.This research has a long-term goal of developing social media as New Informative Media to increase knowledge about HIV-AIDS, so that efforts to increase the incidence of HIV-AIDS can be prevented, especially in adolescents. The method that will be used is action research.This method implemented in two stages. The first phase conducted research on the condition and level of understanding of teenagerÂ about HIV-AIDS and the development of social media that can be delivered in an interesting and informative manner. Specific targets to be achieved in this first phase include: 1) knowing the description of youth knowledge about HIV-AIDS, 2) developing social media forms as an informative medium about HIV-AIDS.The second phase of this research will be the implementation to implement and test the application of the effectiveness of the use of social media in adolescents about HIV-AIDS information. The specific targets that are expected in this second phase include: 1) knowing the response of adolescents to social media as a new media tested, 2) analyzing the results of social media implementation trials, 3) compiling the final social media model about HIV-AIDS, 4) publishing the results of research into local scientific journals that have ISSN or accredited national scientific journals, 5) drafting teaching materials on social media. The results showed that as many as 45.5% of teenagers used the internet 2-3 days, with online duration of more than 4 hours (34.8%), most of the facilities used for internet access using mobile phones (85.2%), while Social media used by teenagers is instagram (25.5%), and whatsapp (23.4%). The type of information opened when the client is an article (35.9%), as well as video (31.3%). Youth knowledge about HIV-AIDS before informational exposure were good (50.2%) and there was an increase in knowledge by 37% using paired sample t test 92-tailed sig. Scores of 0,000 <0.005 after being given health education about HIV-AIDS in adolescents.